Work Productivity Through Compensation, Experiences and Welfare Benefits PT Summit Oto Finance Surabaya - Istanti, Enny; Amaliyah, Amaliyah; GS, Achmad Daeng (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
ABSTRACTÂ Competition in the business world is getting tougher. Companies must be managed dynamically, following the current trends, where the world cannot be separated from technology and the Internet. One of the basic prerequisites for creating competitive advantage is the availability of reliable and competent human resources in accordance with the characteristics of the company. The high level of employee work performance is influenced by several factors including compensation, work experience, and benefits. Compensation, work experience, and welfare benefits are seen as one of the things that can affect the work productivity of employees, because both of these things are now not viewed solely as a means of satisfying material needs but have been one of the basic needs of humans. Hypothesis testing is done based on quantitative tests with relevant statistical test tools. The results of the study state that Compensation, work experience, and welfare benefits have a significant effect on employee work productivity. This is indicated by the probability value of t-count for the variable wages, years of service, and welfare benefits. Compensation has a dominant influence on employee work productivity. This is indicated by the Beta coefficient value for the compensation variable of 0.444 greater than the value of the Beta coefficient variable work experience and welfare benefits.Â Keywords: Work Productivity, Compensation, Experiences, Welfare Benefits